2020
DOI: 10.1016/j.rinam.2019.100089
|View full text |Cite
|
Sign up to set email alerts
|

A high order hybridizable discontinuous Galerkin method for incompressible miscible displacement in heterogeneous media

Abstract: We present a new method for approximating solutions to the incompressible miscible displacement problem in porous media. At the discrete level, the coupled nonlinear system has been split into two linear systems that are solved sequentially. The method is based on a hybridizable discontinuous Galerkin method for the Darcy flow, which produces a mass-conservative flux approximation, and a hybridizable discontinuous Galerkin method for the transport equation. The resulting method is high order accurate. Due to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 48 publications
(58 reference statements)
1
6
0
1
Order By: Relevance
“…11 Recently, the HDG method has been applied in two-phase flow through porous media. [18][19][20] It has all the advantages of the discontinuous Galerkin formulations. This method introduces the trace of the scalar variable as a new unknown.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…11 Recently, the HDG method has been applied in two-phase flow through porous media. [18][19][20] It has all the advantages of the discontinuous Galerkin formulations. This method introduces the trace of the scalar variable as a new unknown.…”
Section: Related Workmentioning
confidence: 99%
“…2,[8][9][10][11][12][13][14][15][16][17] Recently, many efforts have been focused on applying high-order methods to these kind of problems due to their advantages. 11,15,[18][19][20] If the analytical solution is smooth enough, then the numerical solution obtained with a method of order k converges to the analytical one as h k e in L 2 -norm, being h e the element size of the mesh. [21][22][23] Hence, it has been shown that high-order spatial discretization methods can be more accurate than low-order ones for the same mesh resolution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hybridizable discontinuous Galerkin (HDG) methods were first introduced in the last decade by Cockburn et al [1] (see, e.g., [2]) and have since received extensive attention from the research community. They are popular and very efficient numerical approaches for solving a large class of partial differential equations (see, e.g., [3,4,5,6,7] for a historical perspective). Indeed, they inherit attractive features from both (i) discontinuous Galerkin (DG) methods such as local conservation, hp-adaptivity and high-order polynomial approximation [8] and (ii) standard conforming Galerkin (CG) methods such as the Schur complement strategy [9].…”
Section: Introductionmentioning
confidence: 99%
“…Adotando uma combinação de métodos de elementos finitos mistos clássicos com métodos DG, Yang e Chen [59] apresentam uma estratégia de pósprocessamento que resulta em uma superconvergência para a concentração, aumentando a precisão dos resultados da simulação. Métodos híbridos aplicados ao problema acoplado Darcy-Transporte [60,9,61,62,10] apresentam bons resultados. Seja combinados a outras estratégias, seja aproximando ambos os sistemas, sua formulação fica condicionada a imposições do problema modelado, como compatibilização dos espaços de aproximação em problemas mistos ou estabilização dos efeitos convectivos, quando necessário.…”
Section: Lista De Ilustraçõesunclassified